Friday

April 18, 2014

April 18, 2014

Posted by **Hannah** on Monday, November 1, 2010 at 4:16pm.

show that f(e^3) = -e^3

I know you have to substitute e^3 into the function, so Ive sone ths so far:

2e^3 - e^3 ln e^3

What is the next step?

- Maths -
**bobpursley**, Monday, November 1, 2010 at 4:31pm2e^3-e^3lne^3=

2e^3-e^3*3=-e^3

34= ln (e^34)

**Related Questions**

Maths - if f(x) = 2x - x ln x show that f(e^3) = -e^3 I know you have to ...

integration by parts - s- integral s ln (2x+1)dx ? = ln(2x+1)x - s x d( ln (2x+1...

math - Express y as a function of x. C is a positive number. 3 ln y= 1/2ln (2x+1...

Math - Find the derivative of: ln(2x/x+1) the answer is 1/x(x+1) but i can't ...

math - write as a single logarithm: ln(x/x-1)+ ln(x+1/x)- ln(x^2-1) please show ...

Calc - a) y =ln(x-1) find dy/dx=? b) y=3 ln x - ln (1/x) where x >0, dy/dx...

Maths - show that these curves y=2x^2+5x y=x^2+4x+12 y=3x^2+4x-6 have one point ...

MATHS URGENT - The values for x when f(x) = 0 are: x=-2 and x=3 My question is...

calculus - f(x) = x^2 g(x) = e^2x h(x) = ln(2x) which function is increasing the...

Maths - Calculate the area of the surface bounded by the curves representing the...